Rancang Bangun Aplikasi Pelayanan E-Penduduk Berbasis Website Pada Desa Kemang Tanduk - Ovi Resiana; Fajriyah Fajriyah; Phinton Panglipur (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
The population service system has been widely developed by the government to support services to the community, one of the media used by the government is information technology media. The rapid development of technology has greatly influenced people's lives, especially in Indonesia. The Kemang Tanduk village office is the place where village government and population administration services are carried out, especially in Kemang Tanduk village. Population administration services at the Kemang Tanduk village office are still manual, that is, people have to come to the office directly, such as people who want to get a moving certificate, arrival certificate, business certificate and letter of incapacity, they are required to bring their family card as a condition, then the office administration department receives the data and record in the population administration archive book manually. In conducting this research, qualitative research was used, the aim of which was to describe what is currently applicable. So that data will be obtained that supports the preparation of research reports. Meanwhile, in this research, the method used by the author is a qualitative descriptive method, which is a research method that utilizes qualitative data and is described descriptively with the aim of describing or explaining the results of existing research. The software development method that the author uses is the Waterfall model. Meanwhile, analysis and design tools use UML (Unified Modeling Language) consisting of use case diagrams, class diagrams and activity diagrams. This application can provide convenience for people with circumstances or conditions who cannot come directly to the Kemang Tanduk Village office to write letters.